2007
DOI: 10.1002/ijc.22648
|View full text |Cite
|
Sign up to set email alerts
|

Activator protein‐2 in carcinogenesis with a special reference to breast cancer—A mini review

Abstract: Activator protein‐2 (AP‐2) transcription factors are involved in the regulation of cell proliferation, differentiation, apoptosis and carcinogenesis. AP‐2α has been suggested to function as a tumor suppressor in many cancers and AP‐2γ to be a marker of testicular and germ cell malignancies. At least 3 of the 5 AP‐2 family members identified to date, AP‐2α, AP‐2β and AP‐2γ, are known to be expressed in breast tissue and thought to coordinate the growth and development of the breast via regulation of several bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 107 publications
5
100
0
1
Order By: Relevance
“…The transcription factor AP-2 plays a key role in regulating HER-2 gene transcription in breast cancer (11,12). It was reported that AP-2α and AP-2γ are more active than AP-2β in the transcriptional activation of the HER-2 gene induced by multiple growth factor signaling pathways (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription factor AP-2 plays a key role in regulating HER-2 gene transcription in breast cancer (11,12). It was reported that AP-2α and AP-2γ are more active than AP-2β in the transcriptional activation of the HER-2 gene induced by multiple growth factor signaling pathways (35).…”
Section: Discussionmentioning
confidence: 99%
“…Activator protein-2 (AP-2) transcription factors are involved in the regulation of cell proliferation, differentiation, apoptosis, and carcinogenesis (11,12). AP-2α and AP-2γ, as well as AP-2β to some extent, are expressed in HER2/neu-overexpressing breast cancer cell lines alone or in combination and activate the HER-2 promoter in vitro (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…AP-2 family proteins are now recognized as key regulators of carcinogenesis (Pellikainen and Kosma, 2007). Germane to this concept, AP-2 were shown to upor downregulate an increasing number of cancerassociated genes including p21WAF/CIP, transforming growth factor-a, c-Kit, HER-2/neu, MCAM/MUC18 and c-myc (Hilger-Eversheim et al, 2000), VEGF and MMP-2 (BAR-ELI, 2001), and KAI1 (Marreiros et al, 2005) and KiSS-1 (Mitchell et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of these studies, expression of TFAP2A has been associated with a favorable outcome. 3,4 Expression profiling studies in breast cancer 5 have shown that TFAP2A mRNA expression correlated inversely with tumor grade (p < 0.01). This agreed with an immunohistochemical study which reported reduced nuclear TFAP2A staining associated with more aggressive, high-grade breast cancers 6 and a further study which found that TFAP2A levels were highest in normal breast, declined in DCIS cases and were lowest in invasive cancers.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have led to the suggestion that TFAP2A may have a tumor suppressive role, consistent with the observation that its expression level is reduced with advancing stages of breast cancer and also with its suggested role in other cancer types (reviewed in ref. 3). Increased methylation over the first exon of the gene has been proposed as the mechanism behind the progressive loss of TFAP2A expression in invasive breast cancer.…”
Section: Introductionmentioning
confidence: 99%